2017
DOI: 10.1038/s41598-017-11168-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of annexin gene AnnSp2, enhances drought and salt tolerance through modulation of ABA synthesis and scavenging ROS in tomato

Abstract: Drought and high salinity are two major abiotic stresses that significantly affect agricultural crop productivity worldwide. Annexins are a multigene family that plays an essential role in plant stress responses and various cellular processes. Here, the AnnSp2 gene was cloned from drought-resistant wild tomato (Solanum pennellii) and functionally characterized in cultivated tomato. AnnSp2 protein was localized in the nucleus and had higher expression in leave, flower and fruit. It was induced by several phytoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 69 publications
3
66
0
Order By: Relevance
“…An annexin with a high T = 0 expression showed a strong transcript level rise at the higher water deficit (Cc10_g07300, FC = 2.5). Annexins have been linked to drought and oxidative responses, potentially via ABA signaling (Ijaz et al 2017) and this coffee gene was most homologous to Annexin 1 of Arabidopsis, which is a calcium transporter gene known to be induced by water deficits and high temperatures (Huh et al 2010;Liao et al 2017). The two other annexin DEGs (Cc07_g15280 and Cc11_g05800) exhibited only slight transcript increases.…”
Section: Discussionmentioning
confidence: 99%
“…An annexin with a high T = 0 expression showed a strong transcript level rise at the higher water deficit (Cc10_g07300, FC = 2.5). Annexins have been linked to drought and oxidative responses, potentially via ABA signaling (Ijaz et al 2017) and this coffee gene was most homologous to Annexin 1 of Arabidopsis, which is a calcium transporter gene known to be induced by water deficits and high temperatures (Huh et al 2010;Liao et al 2017). The two other annexin DEGs (Cc07_g15280 and Cc11_g05800) exhibited only slight transcript increases.…”
Section: Discussionmentioning
confidence: 99%
“…The association of VCaB42 with vacuoles indicates its possible role in early vacuolar biogenesis (Seals et al, 1997). ANNSp2 was localized in the nucleus (Ijaz et al, 2017) predicting that it may have a transcriptional regulatory role. The fluorescence imaging studies reveals that OsANN5 is localized in the corners of the cells under normal condition.…”
Section: Aba-independent Expression Of Osann5 Under Salt Stressmentioning
confidence: 99%
“…For example, Bianchi et al (2002) suggested that AnnAt1 could be acting downstream of a cross talk between ABA-Auxin. A Solanum pennellii annexin, Annsp2 is associated with ABA accumulation during drought stress when over expressed in tomato and showed insensitivity to external ABA application during the seed germination stage (Ijaz et al, 2017). The annexin, AnnBj2…”
Section: Osann5 Expression Is Possibly Independent Of Aba Under Salt mentioning
confidence: 99%
“…The manifestation of these morphological or physiological responses involves processes starting from perception of stress to the expression of large numbers of genes that increase the chances of survival. Increasing evidence supports that transduction of the stress signal and plant responses are mediated by calcium and the activation of several Ca 2+ sensors [18][19][20]. In Arabidopsis, a study showed that overexpression of the Calmodulin 1 (CaM1) gene positively regulates NADPH oxidase RbohF, leading to abscisic acid (ABA)-triggered ROS production and stomatal closure [21].…”
Section: Introductionmentioning
confidence: 99%